Identifying stress reduction factors in built environment through medical staff involvement - Waroonkun, Tanut; Wejaphikul, Karn; van der Hoeven, Supuck; Chotirat, Jutamat; Pittayaporn, Nitchakarn (Frontiers in Built Environment, 2025)
Physical environment factors in healthcare facilities play an important role in user health and wellbeing, especially among healthcare workers. This research studies the problems, prioritization, and in-depth details of each physical environment factor that affects the stress levels of medical staff. It also seeks to involve medical staff in identifying the built environment factors that influence their stress levels. An examination and comparison of the physical environment factors that affect the mental health and stress of out-patient and pediatric ward staff will also be presented. A three-step data collection process was used: physical environment observation using a checklist, a survey using an analytic hierarchy process (AHP) questionnaire, and individual interviews. Data were collected from 16 medical staff in the pediatric out-patient ward and 17 medical staff in medicine out-patient ward. The observational findings showed that the two out-patient wards had similar environmental problems. AHP ranking findings illustrate that acoustics, privacy, and accessibility were issues of concern for both out-patient ward medical staff. Four different themes emerged from the analysis of the medical staff interviews. Two design recommendations are made to reduce medical staff stress: improving the working environment to decrease stress and improving space management.